"Muting" Neoliberalism? Class and Colonial Legacies in Australia. Issue 2 (July 2013) - Gibson, Chris
Australian governments of left and right persuasions have seemingly embraced elements of the neoliberal agenda, as in many other parts of the world; but exactly how deeply these have been enacted, and how transformative they have been, must be understood in relation to key colonial, geographical and cultural inheritances. These inheritances include the hegemony of central government stewardship of the economy (essential in a colonized, sparsely populated continent of almost unmanageable scale), a long tradition of social democratic regulation, and cultural expectations of socio-spatial equality. Neoliberal policy projects have been "muted" by on-going equality claims, and some progressive "wins" in the social democratic mould have been forthcoming, even while governments have espoused the ascendancy of the market. Nevertheless, neoliberal policy moves have been most starkly felt in worsening income inequalities – where the evidence is unambiguous of a direct threat to the Australian egalitarian ethos.